ACCESS TO DOCUMENTS IN STATE ARCHIVES: THEORETICAL ASPECTS - KONTRIMAVIČIENĖ, DANUTĖ (Knygotyra, 2012)
Access to documents accumulated at state-owned archive repositories is a topical area of scientific research in archivistics. When the paradigms of archivistics shift, the meaning of access to records as well as its place in archival research undergo changes. In the late 20th – early 21st c., archivistics have been moving towards the stage of a postmodern science, and in vigorous discussions of researchers on archivistics paradigms access is reflected as one of the key phenomena of the archival science. When examining access to records, a synonymous term “accessibility” has been established, meaning a granted right (enforced by relevant legislation) to get acquainted with records and availability of the finding aids. Theo Thomassen’s post-preservation or post-modern archivistics, Angelica Menne-Haritz’s access paradigm, Ivano Szekely’s four paradigms of the archives history provide a basis for the access phenomenon in archivistics. Since the object of the archival science has shifted towards archival information, its goal becomes a quality access to information. Access is the mechanism enabling to reach information. Access to documents means the possibility, assured by legislation, of access to information contained within the records, and the existence of appropriate finding aids. At present, following Ivan Szekely’s viewpoint, Lithuania’s state archives could be ascribed to the Public Paradigm, because the Internet access to the documents at state archives is not widespread and not well developed. Therefore, we could state that we are moving to the period of the Global Paradigm. Access to documents may be examined in physical, intellectual, and social aspects.